Collectors, scholars, and forgers in the ancient world object lessons - Higbie, Carolyn (Oxford University Press, 2017)
As early as the Hellenistic era, some Greeks and Romans began to collect objects and might even display them in palaces, villas, or gardens; as these objects acquired value, a demand was created for more of them, and so copyists and forgers created additional pieces - while copyists imitated existing pieces of art, sometimes adapting to their new settings, forgers created new pieces to complete a collection, fill a gap in historical knowledge, make some money, or to indulge in literary play with knowledgeable readers. The study of forged relics is able to reveal not only what artefacts the Greeks and Romans placed value on, but also what they believed they understood about their past and how they interpreted the evidence for it. Drawing on the latest scholarship on forgery and fakes, as well as a range of examples, this book combines stories about frauds with an analysis of their significance, and illuminates and explores the link between collectors, scholars, and forgers in order to offer us a way to better understand the power that objects held over the ancient Greeks and Romans.